(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
Teaching environmental law and climate change issues one may open a number of questions on relations between environmental protection, governmental duties and public rights, starting with: has a government duty to care and maintain a dissent environment and stable climate conditions?; what is a ground for governmental decision-making on actions threatening sustainability of the climate conditions?; where is the beginning and the end of the responsibility of an individual or of an country? The article outlines the elements that provide the criteria under which one may discus on whether it should be the court to force the government to act or should it be a parliament to set laws initiating actions to protect citizens and their human rights from irreversible climate change? The article points out the recent cases State of the Netherlands v. Urgenda Foundation (court decision from December 2019) and Kelsey Cascadia Rose Juliana v. USA (court decision from January 2020). In Urgenda, the court concerned questions: whether the Netherlands is obliged to reduce the emission of greenhouse gases from its soil by at least 25% by the end of 2020 compared to 1990, whether the court can order the State to do so and whether the government is bound to protect human rights in climate crisis? In Juliana, a group of children between the ages of eight and nineteen filed suit against the federal government, claiming that the government violated their constitutional rights by causing dangerous carbon dioxide concentrations. Although the court had found the injury and evidence on causation between government’s actions and climate crisis, it found a lack of redressability. The aim of the article is to examine if the concepts of European Green Deal presented on January 2019 by the Von der Leyen Commission to enshrine the 2050 climate neutrality target into life are in line with conclusions from analysed cases and lessons learned from COVID-19 crisis.